Essays on Bitcoin mining and renewable energy: exploring sustainability and profitability - Hutabarat, Simon Poltak Hamonangan, author; Iverson, Terrence, advisor; Fremstad, Anders, committee member; Shields, Martin, committee member; Burkhardt, Jesse, committee member (Colorado State University. Libraries, 2023)
This Ph.D. dissertation comprises three interlinked studies exploring the intersection of renewable energy economics and cryptocurrency mining, focusing on Bitcoin. Using data from the California Independent Service Operator (CAISO) and a case study from East Indonesia, this research aims to inform energy and financial policies for a sustainable future. The first chapter, "Harnessing Renewable Energy for Cryptocurrency Mining: An Analysis of Locational Marginal Prices in California," looks into the potential of Bitcoin mining to utilize the surplus renewable energy produced during daylight hours when demand is relatively low. It considers whether the Locational Marginal Prices (LMPs) are systematically lower in areas rich in renewable energy resources, presenting an opportunity for strategic Bitcoin mining operations. The second chapter, "Assessing the Impact of Bitcoin Prices on Optimal Mining Hours: Implications for Renewable Energy Development," explores the profitability dynamics of Bitcoin mining. The study discusses the influence of Bitcoin prices and electricity costs on mining operations' profitability, including the ideal hours of operation. The findings suggest that for Bitcoin to be "green" and reduce carbon emissions, the Bitcoin price must be significantly lower than historical averages. The final chapter, "Exploring the Effects of Production Tax Credits on Renewable Energy Development: A Computable General Equilibrium Approach in East Indonesia," evaluates the potential impact of production tax credits (PTCs) on Indonesia's renewable energy industry. This study provides a quantitative assessment of the economic implications of a PTC, contributing to the ongoing debate on incentivizing renewable energy development. Together, these chapters offer insights into the potential of cryptocurrency mining to harness renewable energy, the factors affecting the profitability of Bitcoin mining, and the impact of tax incentives on renewable energy development. These findings could guide policymakers and stakeholders in making informed decisions for a sustainable and profitable future.
Keywords: electricity price; production tax credit; selective mining; energy economics; Bitcoin; renewable energy